Escolas de memórias: representações da escola entre novos letrados (Minas Gerais, décadas de 1900 a 1930) - Cecilia Rodrigues Fadul (2017)
To identifying and analyze the ways in which the school of Minas Gerais of the early twentieth century was learned and told and, to some extent, lived by men and women considered to be new scholars were the fundamental objectives of this work. Its main intention was, therefore, to investigate the school's representations that autobiographers from Minas Gerais born in the late nineteenth or early twentieth century and considered new literates made along their life trajectories. The definition of new literates is based on the concept of "new readers", coined by Jean Hébrard, to designate the first generation of individuals or social groups that carry out, with greater intensity, participation in the cultures of the writing. Thus, the dissertation is based on the studies of Cultural History and, particularly, on the concept of representation, by Roger Chartier. The temporal frameworks covered in this study, considering the time at which the investigated authors were of school age, are comprised between the 1900s and 1930s. Given the specificity of the sources chosen to carry out this research, published between the 1960s and 1980s, a constant dialogue with this period was also present. There is, therefore, the recognition that, at least, two times subsidize autobiographical writing: the moment of the experience and the moment of writing. In order to reach the proposed objectives and considering the type of source chosen for the investigation, seven autobiographies were analyzed, understood as valuable documents to reach the personal experiences of a group that constructed singular representations about the school. It was, therefore, concluded that the school for the new literate was overestimated, especially as a mechanism for inclusion in a society that, over the years between the time of the reported memories and the time of writing saw a growth in the value of schooling and literacy. This society relegated to those who did not acquire such goods, the burden of delay and unpreparedness for life. The authors sought by means of school, reading and writing, in their legitimized uses, to include themselves in the group of those who, by means of knowledge, occupied different places from those (pre)destined for them. The writing of a book the autobiography seemed to shape the ideal outcome of this symbolic ascent.